A Structural Analysis on the Creativity, Self-Leadership, Self-Determination, Career Decision-Making Self-Efficacy, and Career Preparation Behavior of College Students who Participated in the Training Courses from LifeLong Educators - Sin, Park Myeung; Han, Sang-hoon (European Journal of Applied Sciences, 2017)
We conducted a structural analysis on the creativity, self-leadership, self-determination, career decision-making self-efficacy, and career preparation behavior of college students who participated in the training courses of lifelong educators. The results are as follows: First, the creativity has meaningful influence on career preparation behavior. Second, the creativity has meaningful influence on self-leadership, self-determination, and career decision-making self-efficacy. Third, their self-leadership and self-determination, and career decision-making self-efficacy has meaningful influence on career preparation behavior. Fourth, we confirmed that self-leadership, self-determination, and career decision-making self-efficacy have meaningful mediation influence between the creativity, and career preparation behavior.